The determination of the optimal strip‐thickness of anti‐scatter grids for a given grid ratio and strip height. Issue 4 (13th February 2020) - Zhou, Abel; Yin, Yuming; Tan, Qi; L. White, Graeme; Davidson, Rob
Abstract: In X‐ray imaging, anti‐scatter grids are used to reduce scatter radiation reaching image receptors, hence improving image quality. Optimization of grid performance is essential for improving image diagnostic quality and minimizing radiation doses to patients. This work investigated the performance of a series of grid designs modeled from the design of typically focused grid with grid ratio 8:1 (r8) and strip height 1.7 mm (h1.7) for high‐energy radiographic applications. Monte Carlo simulation was used to evaluate designs (r8h1.7) which had the strip thickness changed from 6 to 150 μm in 2 μm increments and the interspace distance fixed at 214 μm. The transmissions of radiation in grid materials were modeled by using a regression with radial‐basis‐function‐networks (RBFNS). K SNR was then determined from RBFNS models of radiation transmissions. The optimal strip‐thickness was obtained at the maximum signal‐to‐noise ratio (SNR) improvement factor ( K SNR ). For high‐energy applications at 100 peak‐kilo‐voltage (kVp) and 30 cm PMMA thickness, the optimal lead‐strip‐thickness was found approximately 74 μm resulting in a strip‐frequency approximately 35 per cm (N35). Using the optimal thickness for imaging condition at 100 kVp and 30 cm thickness, the K SNR would increase by approximately 5.3%. This work showed the existence of optimal strip‐thickness for a series of grids with a given grid‐ratio, strip‐height, strip‐, and interspace materials. The findings are useful and provide guidance to improve grid designs for better performance that will essentially lead to better image quality and better radiation protection for patients.